Analysis of the abundance and mistletoe infection in Sierra Fría, Aguascalientes, México - Clark-Tapia, Ricardo; Torres-Bautista, Brenda; Alfonso-Corrado, Cecilia; Valdez-Hernández, Juan I.; González-Adame, Gabriel; Bretado-Velázquez, Jorge; Campos-Contreras, Jorge (Instituto de Ecología, A.C., 2016)
Mistletoe, a hemiparasitic plant, is the second most destructive agent for Mexican forests after the bark beetle.  For this reason, in the present study, its infestation in the forest populations of Sierra Fría, Aguascalientes was examined in order to: a) understand the factors that influence the abundance of mistletoe; (b) determine the infestation level present in host species and (c) identify if there exists specific types of mistletoe that correspond to different species and sizes of the host and / or habitat. In January 2007, 20 sampling locations were selected within which two sampling units were established (UM) of 2500 m2. In every UM the height and diameter of all individuals (infected and uninfected) > 1 m in height were measured and the presence of mistletoe was recorded. Also recorded was the altitude, incline, slope orientation, level of disturbance and degree of infestation. The results indicate that the level of mistletoe infection shows positive association with altitude and orientation and a negative association with disturbance. It was found that as the size of dasometric attributes (height, diameter) increases so too does the degree of infection. Phoradendron bolleanum was the most abundant species of mistletoe, with Juniperus deppeana being its most common host. In contrast to that reported by other works, Sierra Fría forest populations are not found to be severely affected by mistletoe. Nevertheless, it is recommended that future studies be undertaken that allow for the understanding of the factors that shape the distribution and hemiparasitic-host interaction within and between populations, in order to assess real or future damage and to evaluate the selectivity towards certain host species and chemical changes from which trees suffer as a result of infection.